International consensus on ANA patterns (ICAP): the bumpy road towards a consensus on reporting ANA results - Damoiseaux, Jan; von Mühlen, Carlos A.; Garcia-De La Torre, Ignacio; Carballo, Orlando Gabriel; de Melo Cruvinel, Wilson; Francescantonio, Paulo Luiz Carvalho; Fritzler, Marvin J.; Herold, Manfred; Mimori, Tsuneyo; Satoh, Minoru; Andrade, Luis E. C.; Chan, Edward K. L.; et al. (Autoimmunity Highlights, 2016)
The International Consensus on ANA Patterns (ICAP) was initiated as a workshop aiming to thoroughly discuss and achieve consensus regarding the morphological patterns observed in the indirect immunofluorescence assay on HEp-2 cells. One of the topics discussed at the second ICAP workshop, and addressed in this paper, was the harmonization of reporting ANA test results. This discussion centered on the issue if cytoplasmic and mitotic patterns should be reported as positive or negative. This report outlines the issues that impact on two major different reporting methods. Although it was appreciated by all participants that cytoplasmic and mitotic patterns are clinically relevant, implications for existing diagnostic/classification criteria for ANA-associated diseases in particular hampered a final consensus on this topic. Evidently, a more concerted action of all relevant stakeholders is required. Future ICAP workshops may help to facilitate this action.